Research on skid control system of small electric vehicle : (the effect of regenerative brake control on in-wheel small electric vehicle with anti-lock brake system) - Muhammad Izhar, Ishak (2013)
In the conventional diesel and gasoline vehicle, the engine output is delivered to the wheels through several mechanical components include transmission, driveshaft and differential. However, with in-wheel motor, electric power is transferred directly to each wheel via signal cables, eliminating the possibility of energy loss and provides excess free space to install other components such as servo motor which is needed- .to-steer the wheel independently. The objective of this research is to validate a control method for complex mathematical model of a four wheel steering small electric vehicle by investigating the steering performance during braking of a two wheel drive (2WD) small electric vehicle with hydraulic mechanical hybrid brake system. A 2WD small electric vehicle was used to determine all possible parameters that are going to be used throughout the research Due to only braking condition is taken consideration, an anti-lock brake systems was evaluated as a basic skid contrOl system. In order to achieve the objective, investigations was done by using a Visual Studio numerical simulation. The current electric vehicle (Toyota COMS) features was used as a model in the simulation. A few alterations were made in the simulation whereas the current EV was not equipped with an ABS. The experimental result of the steering performance during different road; which was dry asphalt and icy road, and driving condition was evaluated to set the parameters and acquires the proper control method.